An Overview of HPV Screening Tests to Improve Access to Cervical Cancer Screening Amongst Underserved Populations: From Development to Implementation - Okunade KS; Adejimi AA; John-Olabode SO; Oshodi YA; Oluwole AA (Dove Medical Press, 2022)
Kehinde S Okunade,1 Adebola A Adejimi,2 Sarah O John-Olabode,3 Yusuf A Oshodi,4 Ayodeji A Oluwole1 1Department of Obstetrics & Gynaecology, College of Medicine, University of Lagos, Lagos, Nigeria; 2Department of Community Health and Primary Care, College of Medicine, University of Lagos, Lagos, Nigeria; 3Department of Haematology and Blood Transfusion, College of Medicine, University of Lagos, Lagos, Nigeria; 4Department of Obstetrics & Gynaecology, Lagos State University College of Medicine, Lagos, NigeriaCorrespondence: Kehinde S Okunade, Department of Obstetrics and Gynaecology, College of Medicine, University of Lagos, Lagos, Nigeria, Email sokunade@unilag.edu.ngAbstract: Cervical cancer is the most common human papillomavirus (HPV)-related disease. Knowledge of the natural history and aetiology of cervical cancer offers unique opportunities for its prevention, and the development of HPV screening tests is one of the most effective strategies. The current HPV diagnostics detect HPV DNA or E6/E7 mRNA in cervical/vaginal samples using molecular-based technologies. HPV screening tests are more sensitive than cytology or visual inspection with acetic acid (VIA) as a primary screening method and are even more clinically valuable in triaging mild cytological abnormalities as a hybrid test. As technical and laboratory resources are grossly limited in marginalized or underserved settings which thus require that women travel long distances for screening and treatment. The practical implementation of an HPV-based screening programme may face many challenges and measures should be instituted to overcome these challenges without compromising disease detection. These measures may include a reduction in screening frequency using the WHO global strategy of offering HPV screening tests at 35 and 45 years of age, adoption of a high throughput testing technology, and improved access to vaginal HPV self-sampling screening tests to women in remote settings or those who are reluctant to undergo gynecologic examination. Another important strategy is the implementation of a "see-and-treat" approach using a point-of-care platform that requires limited skills of laboratory technicians. In addition, the development and large-scale incorporation of more specific HPV testing technologies that are much cheaper and easier to use in non-laboratory settings than the currently available options should be prioritized for underserved settings. At the same time, there is a need to develop and commence the implementation of an affordable and readily available intermediate or secondary test with optimal specificity for triaging or segregating clinically unimportant HPV infections that do not require colposcopy.Keywords: cervical cancer, cytology, E6/E7 mRNA, HPV self-sampling, VIA